Football in Asia history, culture and business - Cho, Younghan (Sport in the global society. Contemporary perspectives, 2015)
This book is the first comprehensive study on history, culture, and business of football in Asia. Football has been a symbol of the modern invention, a catalyst of local, national and regional identities, all time favourite among kids and youths, and even a harbinger for cultural globalization and consumerism in Asia. The economic growth and the current proliferation of football culture in Asia make it imperative to examine the complex relationship between the globalization of football and the local appropriation. The essays in the book deal with various topics on football in Asia from history of football in Asia, football and local, national and regional identities, to commercialization of football cultures, global mobility and athletes' migration, and then new Asianism and football. This book argues that football in Asia contributes to reconfiguring both national and regional identities among football fans in the active interconnection with the global flows of football and cultural globalization without homogenizing Asian identities into a cosmopolitan one.